Exploring biodiversity the search for new medicines - Bonnie L. Bassler, lecturer; Baldomero M. Olivera, lecturer (Howard Hughes Medical Institute, 2010)
Two leading biologists discuss their paths of medical discovery based on a deeper understanding of biodiversity. Bonnie L. Bassler examines the molecular mechanisms that bacteria use to communicate with one another. Baldomero Olivera conducts research using the venomous predatory cone snail which has led to a better understanding of ion channels and identification of several therapeutic drug candidates.